Impact of Diverse Plant Growth Regulators on Quality Traits of Garlic (Allium sativum L.) - Seelothu, Rakesh; Medda, P. S.; Dutta, Babli; Ghosh, Arunava; Khalko, Surajit (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted at the instructional cum research farm of the Department of Plantation Crops and Processing of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, India during rabi season for consecutive two years (October-2019 to March-2020 and October-2020 to march-2021) to investigate the “Effect of Different Plant Growth Regulators on Quality attributes of Garlic (Allium sativum L.)” with various growth regulators (GA3@ 50 ppm, GA3 @ 100 ppm, GA3 @ 150 ppm, NAA @ 50 ppm, NAA @ 100 ppm, NAA @ 200 ppm, Kinetin @ 10 ppm, Kinetin @ 20 ppm, Kinetin @ 40 ppm and Control (Distilled water). In view of, effect of different plant growth regulators on quality attributes has observed significant variation. Results pertaining to total soluble solids, significantly highest TSS recorded under GA3 @100 ppm treated plots (32.10 °Brix), however, dry matter content of bulb was highest at GA3 @ 50 ppm (33.63%). Interestingly, highest oleoresin content of the bulb was also reported from the GA3 @ 50 ppm treated plots (0.24 g) with lowest physiological loss of bulb weight (7.04%). The control plots treated with distilled water was produced qualitatively inferior bulbs. The aim of the study provided valuable results to determine the potential growth regulator for enhancing post-harvest quality attribute of garlic by employing methodology of Randomized Block Design comprising of three replications with ten treatments. Based on the current experimental results, it may be concluded that foliar application of GA3 @ 50 ppm proved the best over other plant growth regulators.